2011
DOI: 10.3899/jrheum.100954
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Musculoskeletal Pain and Rheumatic Diseases in the Southeastern Region of Mexico. A COPCORD-Based Community Survey

Abstract: The prevalence of MSK pain was 19.6%. MSK pain was more prevalent in women and in the urban setting. A remarkably high prevalence of RA was found in this population, which suggests a role for geographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 27 publications
0
29
2
4
Order By: Relevance
“…Epidemiologic studies have shown that the frequency of AS and SpA in a given population parallels the frequency of HLA-B27 22-36 (Tables 3-4). In early axial SpA, one recent study has shown that HLA-B27 is associated with earlier onset of IBP, less delay in diagnosis, axial inflammation (spine and sacroiliac joints), radiographic damage of the sacroiliiac joint, decreased disease activity, and lower frequency of psoriasis, but not with physical function and MRI structural lesions of the sacroiliac joints 37 .…”
Section: The Importance Of Hla-b27 In Axspa and Asmentioning
confidence: 99%
“…Epidemiologic studies have shown that the frequency of AS and SpA in a given population parallels the frequency of HLA-B27 22-36 (Tables 3-4). In early axial SpA, one recent study has shown that HLA-B27 is associated with earlier onset of IBP, less delay in diagnosis, axial inflammation (spine and sacroiliac joints), radiographic damage of the sacroiliiac joint, decreased disease activity, and lower frequency of psoriasis, but not with physical function and MRI structural lesions of the sacroiliac joints 37 .…”
Section: The Importance Of Hla-b27 In Axspa and Asmentioning
confidence: 99%
“…Studies from Latin-America and Africa are scarce. A community-based COPCORD door-to-door study in 4059 subjects aged older than 18 years in Mexico, estimated a prevalence of AS of 0.02% [73]. AS is virtually absent in African blacks.…”
Section: Literature Review On Prevalence and Incidence Spamentioning
confidence: 99%
“…In late May, the CMR prepared a table of specifications and a skills matrix, using the academic content of the Rheumatology course 13 and considering the estimated prevalence in our country 14 of rheumatic diseases. The final proposal included the design of 14 stations, with well-defined 7 requirements.…”
Section: Methodsmentioning
confidence: 99%